2014
DOI: 10.4253/wjge.v6.i10.493
|View full text |Cite
|
Sign up to set email alerts
|

What can be the criteria of outpatient-based endoscopic resection for colon polyp?

Abstract: AIM:To investigate whether out-patient based endoscopic mucosal resection (EMR) for colon polyps ≤ 10 mm is safe. METHODS:Between January 2004 and December 2012, a total of 3015 EMR cases conducted in 1320 patients were retrospectively reviewed. The factors contributing delayed hemorrhage were analyzed. We calculated the probability of delayed bleeding after stratifying conditions of specific risk factors. RESULTS:The size of the polyp (95%CI: 1.096-1.164, P < 0.001) and patients with chronic renal failure (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In EMR group, 40 studies (Swan et al, 2009;Su et al, 2005;Bories et al, 2006;Katsinelos et al, 2006;Arebi et al, 2007;Hurlstone et al, 2008;Urban et al, 2008;Mahadeva and Rembacken, 2009;Luigiano et al, 2009;Huang et al, 2009;Lim et al, 2010;Ferrara et al, 2010;Saito et al, 2010a;Toyonaga et al, 2010;Hochdörffer et al, 2010;Moss et al, 2011;Kao et al, 2011;Tajika et al, 2011;Santos et al, 2011;Mannath et al, 2011;Kim et al, 2012Kim et al, , 2013Kim et al, , 2014Lee et al, 2012;Kobayashi et al, 2012;Fasoulas et al, 2012;Buchner et al, 2012;Terasaki et al, 2012;Carvalho et al, 2013;Masci et al, 2013;Dior et al, 2013;Cipolletta et al, 2014;Maguire and Shellito, 2014;Gómez et al, 2014;Grgov et al, 2014;Belle et al, 2014;Knabe et al, 2014;Hong et al, 2015;Oka et al, 2015;Voudoukis et al, 2015) reported results about standard EMR (inject and cut technique), Cap-assisted EMR (EMRC) was reported in 3 studies (Bergmann and Beger, 2003;…”
Section: Resultsmentioning
confidence: 96%
“…In EMR group, 40 studies (Swan et al, 2009;Su et al, 2005;Bories et al, 2006;Katsinelos et al, 2006;Arebi et al, 2007;Hurlstone et al, 2008;Urban et al, 2008;Mahadeva and Rembacken, 2009;Luigiano et al, 2009;Huang et al, 2009;Lim et al, 2010;Ferrara et al, 2010;Saito et al, 2010a;Toyonaga et al, 2010;Hochdörffer et al, 2010;Moss et al, 2011;Kao et al, 2011;Tajika et al, 2011;Santos et al, 2011;Mannath et al, 2011;Kim et al, 2012Kim et al, , 2013Kim et al, , 2014Lee et al, 2012;Kobayashi et al, 2012;Fasoulas et al, 2012;Buchner et al, 2012;Terasaki et al, 2012;Carvalho et al, 2013;Masci et al, 2013;Dior et al, 2013;Cipolletta et al, 2014;Maguire and Shellito, 2014;Gómez et al, 2014;Grgov et al, 2014;Belle et al, 2014;Knabe et al, 2014;Hong et al, 2015;Oka et al, 2015;Voudoukis et al, 2015) reported results about standard EMR (inject and cut technique), Cap-assisted EMR (EMRC) was reported in 3 studies (Bergmann and Beger, 2003;…”
Section: Resultsmentioning
confidence: 96%
“…At present, colon adenoma-colon cancer sequential theory has been accepted by the vast number of medical workers, the diagnosis of colonic polyps is of great significance for the prevention of colon cancer [8]. Foreign related research reports [9], the common cause of lower digestive tract hemorrhage are intestinal diverticulum, ischemic bowel disease, perianal disease, in this study, the common causes of lower digestive tract hemorrhage are ulcerative colitis, colorectal polyps, ischemic bowel disease, perianal disease (hemorrhoids), this difference may be related to different living habits, environmental factors and ethnic differences between China and foreign countries.…”
Section: Discussionmentioning
confidence: 99%
“…Not eligible studies were excluded because of absence of data about ASA/NSAIDs, absence of data about bleeding or if there were reviews or commentary. Sixteen studies were finally included in the qualitative analysis (5,6,(8)(9)(10)12,(14)(15)(16)(17)(27)(28)(29)(30)(31)(32). Because of lack of sufficient explanation in the methods about exposure to ASA/NSAIDs, five more studies [6,8,[28][29][30] were excluded.…”
Section: Study Selectionmentioning
confidence: 99%
“…Nonetheless, the reported percentage of post-polypectomy bleeding [PPB) ranges from 0.07-1.7% [2][3][4]. Prior studies recognized some features related to PPB, as polyp size, position in the right colon, sessile morphology, number of polyps, comorbidities, endoscopist's experience and use of antiplatelet/anticoagulant drugs [4][5][6][7][8][9][10][11][12]. There are no high quality evidences for an association between antiplatelet drugs and PPB.…”
Section: Introductionmentioning
confidence: 99%